Estimación de la disposición a pagar por panela ecológica desde el enfoque del consumo sostenible - Roa, Zulma (2004)
Estimating the value of the environmental services represents a crucial element in the process of making decisions on the programs and the environmental politics to develop, as well as an orientation instrument for the implementation of production patterns and more sustainable consumption. From this perspective, the present study has as purpose to estimate the willingness to pay (WTP) of the consumers from Bogotá for ecological panela2 valuation was used. A selected stratified sampling of the population was determined by socioeconomic stratum for the city of Bogotá; the consumers were asked if they would be willing to pay for ecological panela, as well as topics related to their consumption behavior, likes, preferences, environmental, social commitment, and their socioeconomic characteristics. By means of the combination of this method of economic valuation and qualitative information, this paper concluded that the consumers are willing to pay a bigger price for these panela types, especially for the powder ecological panela. A crucial conclusion is the existence of a direct relationship between the socioeconomic stratum and the WTP by conventional and ecological powder panela. Finally, it was determined that the commitment for the conservation and protection of the environment, when it is perceived by the consumer like an element that guarantees the consumption of healthy and innocuous products, represents a decisive factor in the willing to pay a bigger price for conventional and ecological powder panela.